Proteksi Motor Induksi Satu Fasa Terhadap Kenaikan Suhu Pada Pengering Maggot Berbasis Panel Surya - Asri Indah Lestari; Sofiah, Sofiah; Yogie Ragil Pamungkas (Jurnal Ampere, 2023)
Electric motors are a very vital need in an industry, household and other needs. Electric motors that are often used in an industry are types of induction motors, where the induction machine is an electric motor that is very easy in its maintenance system so that this motor has the highest rating in its use system. In this study, using a single-phase induction motor as a maggot dryer is useful for making the maggot storage period longer and of high selling value. This study aims to protect the single-phase induction motor in the maggot drying system against temperature increase due to prolonged grinding using the DS18B20 sensor. So that the single-phase induction motor is able to work when the motor is unstable at the time of overcurrent. With the installation of the DS18B20 sensor, the single-phase induction motor will stop automatically when the given temperature setting has exceeded the limit set on the sonoff.  With the protection system of this single-phase induction motor, it can maximize the performance of the electric motor in the maggot drying process and provide convenience in remote motor control and time setting on and off using the Internet of Things (IoT).